Guidance for the Management of Patients with Vascular Disease or Cardiovascular Risk Factors and COVID-19: Position Paper from VAS-European Independent Foundation in Angiology/Vascular Medicine - Gerotziafas, Grigoris T; Catalano, Mariella; Colgan, Mary-Paula; Pecsvarady, Zsolt; Wautrecht, Jean Claude; Fazeli, Bahare; Olinic, Dan-Mircea; Farkas, Katalin; Elalamy, Ismail; Falanga, Anna; Fareed, Jawed; Papageorgiou, Chryssa; et al. (Thrombosis and haemostasis, 2020)
COVID-19 is also manifested with hypercoagulability, pulmonary intravascular coagulation, microangiopathy, and venous thromboembolism (VTE) or arterial thrombosis. Predisposing risk factors to severe COVID-19 are male sex, underlying cardiovascular disease, or cardiovascular risk factors including noncontrolled diabetes mellitus or arterial hypertension, obesity, and advanced age. The VAS-European Independent Foundation in Angiology/Vascular Medicine draws attention to patients with vascular disease (VD) and presents an integral strategy for the management of patients with VD or cardiovascular risk factors (VD-CVR) and COVID-19. VAS recommends (1) a COVID-19-oriented primary health care network for patients with VD-CVR for identification of patients with VD-CVR in the community and patients' education for disease symptoms, use of eHealth technology, adherence to the antithrombotic and vascular regulating treatments, and (2) close medical follow-up for efficacious control of VD progression and prompt application of physical and social distancing measures in case of new epidemic waves. For patients with VD-CVR who receive home treatment for COVID-19, VAS recommends assessment for (1) disease worsening risk and prioritized hospitalization of those at high risk and (2) VTE risk assessment and thromboprophylaxis with rivaroxaban, betrixaban, or low-molecular-weight heparin (LMWH) for those at high risk. For hospitalized patients with VD-CVR and COVID-19, VAS recommends (1) routine thromboprophylaxis with weight-adjusted intermediate doses of LMWH (unless contraindication); (2) LMWH as the drug of choice over unfractionated heparin or direct oral anticoagulants for the treatment of VTE or hypercoagulability; (3) careful evaluation of the risk for disease worsening and prompt application of targeted antiviral or convalescence treatments; (4) monitoring of D-dimer for optimization of the antithrombotic treatment; and (5) evaluation of the risk of VTE before hospital discharge using the IMPROVE-D-dimer score and prolonged post-discharge thromboprophylaxis with rivaroxaban, betrixaban, or LMWH.
Keywords: heparin nízkomolekulární; COVID-19; lidé; COVID-19 Drug Treatment; kardiovaskulární nemoci; Risk Factors; Anticoagulants; Heparin, Low-Molecular-Weight; Evropa; Societies, Medical; Thrombophilia; Cardiology; rivaroxaban; Thrombosis; Humans; Inflammation; kardiologie; zánět; Practice Guidelines as Topic; společnosti lékařské; Cardiovascular Diseases; SARS-CoV-2; Rivaroxaban; trombofilie; směrnice pro lékařskou praxi jako téma; farmakoterapie COVID-19; Europe; trombóza; rizikové faktory; antikoagulancia